Do the school adaptation levels of preschoolers vary according to their relationship with their teachers? - Filiz Erbay; Neslihan Durmuşoğlu Saltalı (Institute of Advanced Engineering and Science, 2020)
In this study, the differentiation status of preschool children's adaptation to school according to their relationship with teachers was examined. The study participants consisted of 326 children aged 60-72 months and 21 preschool teachers in different preschool educational institutions affiliated to the Provincial Directorate of National Education in Konya, Turkey. The School Adaptation Teacher Assessment Scale and Teacher-Student Relationship Scale were utilized to collect the research data. In the evaluation of the research data, firstly, teacher-child relationship scores were divided into groups for cluster analysis: conflictual/non-conflictual, dependent/ independent, and close/distant teacher-child relationship. The data gathered were analyzed using the independent-samples t-test. The results of the study revealed that the level of school adaptation of the children who had close, non-conflictual, and independent relationships with their teachers differed significantly from that of children who had distant, conflictual, and dependent relationships with their teachers. Positive teacher-child relationships reflected positively on the level of the child's school adaptation level. Teachers should establish close relationships with children in order to facilitate their adaptation to the school in the preschool period.